2017
DOI: 10.1002/pssb.201700552
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stress Effect on the Structure and Properties of Single and Double Stacked Films of GeTe and SnSe

Abstract: The thermal stress effect on the structure of phase change memory materials, namely single films and double stacked films of GeTe and SnSe, is evaluated. The crystallization temperatures of GeTe and SnSe single films are 138 °C and 292 °C, respectively. The films are amorphous before annealing and crystallize in rhombohedral and orthorhombic structures afterwards. Ge is tetrahedrally bonded and Se is bivalent after deposition. Both Ge and Se have an octahedral configuration after annealing. The double stacked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Besides, the thermoelectric properties of SnSe at moderate and low temperature scales need to be further improved. [33] Many studies have been devoted to improving the thermoelectric properties of SnSe at moderate and low temperatures. [34][35][36][37][38][39][40] For example, the ZT value of Na-doped SnSe can be as high as 2.0 and Bi-doped SnSe reached 2.2.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the thermoelectric properties of SnSe at moderate and low temperature scales need to be further improved. [33] Many studies have been devoted to improving the thermoelectric properties of SnSe at moderate and low temperatures. [34][35][36][37][38][39][40] For example, the ZT value of Na-doped SnSe can be as high as 2.0 and Bi-doped SnSe reached 2.2.…”
Section: Introductionmentioning
confidence: 99%
“…The MS sample is not completely crystalline: it has 18% amorphous phase left. It was shown that the films obtained by magnetron sputtering crystallize at a higher temperature than in the case of PLD [10,30]. On the other hand, in the other two samples (PLD and MSPLD), a minor hexagonal GeSb 4 Te 4 is obtained, which can be regarded as a seed for the hcp-GST-225 formation at a higher annealing temperature [3].…”
Section: X-ray Diffractionmentioning
confidence: 95%
“…[12] Another proposed approach is to stack different films of memory materials. [13][14][15] However, these approaches are either complex from a fabrication point of view or difficult to control to achieve multiple resistive states.…”
mentioning
confidence: 99%